INFEKSI JAMUR KUKU (ONYCHOMYCOSIS) PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA WANA SERAYA: ONYCHOMYCOSIS IN ELDERLY AT WANA SERAYA NURSING HOME - Aryasa, I Nyoman; Bintari, Ni Wayan Desi; Sudarsana, I Dewa Agung Ketut (Bali Medika Jurnal, 2020)
Onychomycosis is an infection of the nail plate that can be caused by dermatophyte fungi (Tinea unguium), non dermatophytes or yeast. Onychomycosis infection causes damage to the nails which causes the nail plate to thicken, brittle and break easily. This study aims to describe onychomycosis in the elderly at Tresna Werdha Social Home (PSTW) Wana Seraya. This type of research is descriptive research. Sampling was conducted at the Tresna Werdha Social Home (PSTW) Wana Seraya on 66 Gemitir St., Kesiman Kertalangu, East Denpasar, Denpasar City, Bali. Samples analyzed in Parasitology Laboratory STIKes Wira Medika Bali. Sampels examination using direct observation techniques using 10% potassium hydroxide (KOH) dye on nail scrapings on 15 respondents who met the inclusion and exclusion criteria. The results of the examination showed that there was 1 respondent (6.67%) who tested positive for onychomycosis with the discovery of hyphae on microscopic observation of nail scrapings preparations. Meanwhile 14 other samples (93.33%) were stated negative. The screening results in this study show that the elderly in PSTW Wana Seraya have had good personal hygiene, especially in maintaining the cleanliness of toenails and hands, thereby reducing the risk factors for nail fungus infection.